Studi Empiris tentang Pengaruh Komunikasi Pemasaran dan Kualitas Produk terhadap Keputusan Pembelian pada UMKM Warkop Rencong Medan - Adelina Lubis; Ihsan Effendi; Olivia Sembiring; Naila Zuhra (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
This study aims to explore and analyze how marketing communication and product quality influence consumer purchasing decisions at Warkop Rencong, an MSME located in Medan. In a highly competitive local food industry, implementing effective marketing communication strategies and maintaining high product quality are essential elements that drive consumer behavior. Marketing communication not only informs consumers about the product but also builds a perspective and emotional connection with them. Product quality, on the other hand, reflects how well the product meets consumer expectations and needs, fostering customer satisfaction and long-term loyalty. This research adopts a quantitative approach, utilizing questionnaires to gather data from 60 respondents selected through random sampling from Warkop Rencong's active customer base. The collected data were analyzed using validity, reliability, classical assumptions, and multiple linear regression tests in IBM SPSS Statistics 27. The results indicate that both marketing communication and product quality significantly and positively influence purchasing decisions, both individually and collectively. Product quality was found to have a stronger impact on purchasing decisions compared to marketing communication. The F-test confirms that both variables significantly affect purchasing decisions, with an adjusted R² of 0.532, indicating a high explanatory power of the model. These findings offer practical insights for MSMEs in developing effective marketing strategies and ensuring high product quality to boost consumer purchasing decisions.